2015
DOI: 10.2147/tcrm.s94889
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-sodium dialysate on ambulatory blood pressure measurement parameters in patients undergoing hemodialysis

Abstract: BackgroundEnd stage renal disease is related to increased cardiovascular mortality and morbidity. Hypertension is an important risk factor for cardiovascular disorder among hemodialysis (HD) patients. The aim of this study was to investigate the effect of low-sodium dialysate on the systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels detected by ambulatory BP monitoring (ABPM) and interdialytic weight gain (IDWG) in patients undergoing sustained HD treatment.Patients and methodsThe study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…We previously found that dialysate sodium profiling can reduce postdialysis BP in hypertensive patients on maintenance hemodialysis [12]; in the current study, we further identified that dialysate sodium profiling, compared to regular dialysate sodium status, effectively decreases interdialytic ABP and use of antihypertensive medication. Another study similarly showed that low-sodium dialysate can reduce morning and night ABP over a period of six months [13]. Inrig et al [14] conducted a randomized study, comparing hemodialysis patients receiving low-and high-sodium dialysate for three weeks, and found that low-sodium dialysate leads to a mean 9-mmHg decrease in systolic BP, consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…We previously found that dialysate sodium profiling can reduce postdialysis BP in hypertensive patients on maintenance hemodialysis [12]; in the current study, we further identified that dialysate sodium profiling, compared to regular dialysate sodium status, effectively decreases interdialytic ABP and use of antihypertensive medication. Another study similarly showed that low-sodium dialysate can reduce morning and night ABP over a period of six months [13]. Inrig et al [14] conducted a randomized study, comparing hemodialysis patients receiving low-and high-sodium dialysate for three weeks, and found that low-sodium dialysate leads to a mean 9-mmHg decrease in systolic BP, consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…They noted reduced IDWG from 2.3±0.9 to 1.6±0.6 kg ( P <.001) in the interventional group as well as lower ambulatory blood pressure (24‐hour SBP 136±22 at baseline to 127±19 mm Hg after 6 months, P <.05; Daytime SBP 138±22 to 130±19, P <.05; Nighttime SBP 131±26 to 120±27, P <.05; Nighttime DBP 69±11 to 64±8, P <.05) and blood pressure medications (2.1±0.8 to 1.2±0.4, P <.001), with nonsignificant changes in the standard D‐Na group. Three patients withdrew from the low D‐Na arm because of cramps or lDH …”
Section: Intermediate Outcomes After Universal Reductions In Dialysatmentioning
confidence: 99%
“…IDWG at baseline and 12 months was in the intervention group 3.3 ± 0.7 kg and 2.8 ± 0.6 kg ( p < 0.05) and, in the control group, 3.1 ± 0.8 kg and 3.0 ± 1 kg ( p > 0.05). Akdag et al [ 38 ] randomized 46 patients, dialyzed with 140 dialysate sodium concentration, into a control group (24 patients) that maintained the dialysate 140 mmol sodium concentration and a treatment group in which the dialysate sodium concentration was reduced to 137 mmol/l. IDWG at baseline and 6 months was, in the intervention group, 2.2 ± 0.9 kg and 1.6 ± 0.5 kg ( p < 0.001) and, in the control group, 2.3 ± 0.8 kg and 2.1 ± 0.7 kg ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%